Сутичка героя з вілою через побудову намету - Делич, Л. (Народна творчість та етнологія, 2012)
The paper examines the conflict between a hero (Marko Kraljević and Banović Strahinja / Sibinjanin Janko) and a nixie over the building of a tent from the point of view of an archaic (that is concerned with cosmogony and initiation) patterns and symbolic meanings, as well as the interaction between the hero and a particular model of a sujet.